2014
DOI: 10.1021/jp501670g
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Origin of Performance Improvement and Fade for 4.6 V LiNi0.5Co0.2Mn0.3O2 Battery Cathodes

Abstract: The interfacial origin of performance improvement and fade of high-voltage cathodes of LiNi 0.5 Co 0.2 Mn 0.3 O 2 for high-energy lithium-ion batteries has been investigated. Performance improvement was achieved through interfacial stabilization using 5 wt % methyl (2,2,2-trifluoroethyl) carbonate (FEMC) of fluorinated linear carbonate as a new electrolyte additive. Cycling with the FEMC additive at 3.0−4.6 V versus Li/Li + results in the formation of a stable solid electrolyte interface (SEI) layer and effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
136
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 47 publications
10
136
0
1
Order By: Relevance
“…The results in Figure highlight an additional finding about the composition of the positive electrode interphase (PEI) layer of the aged electrode . Even after rinsing of the extracted aged electrode with dimethyl carbonate (DMC), the white surface layer of material seen in Figure b, and again in Figure a, was found to persist (with varying thickness) across most of the PEI region.…”
mentioning
confidence: 64%
“…The results in Figure highlight an additional finding about the composition of the positive electrode interphase (PEI) layer of the aged electrode . Even after rinsing of the extracted aged electrode with dimethyl carbonate (DMC), the white surface layer of material seen in Figure b, and again in Figure a, was found to persist (with varying thickness) across most of the PEI region.…”
mentioning
confidence: 64%
“…Extensive efforts have therefore been made to further improve the electrochemical performance of LIBs, and especially to search for high capacity cathode materials. Layered lithium transition metal (TM) oxides, which have the -NaFeO2 structure and the general chemical formula, LiNixMnyCozO2 (NMC) (x+y+z=1), are cathode materials that are currently under extensive studies with the high theoretical capacity of about 280 mAh g -1 [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it can be rationally concluded that the preformed SEI protector can suppress the electrolyte decomposition and stabilize the graphite cathode during the successive cycles, facilitating the PF 6 ‐ de‐/intercalation from/into graphene layers. Moreover, the low content of Li x PO y F z on SMG indicates the high possibility of PF 6 ‐ to occur the de‐/intercalation reactions rather than the decomposition on the surface of graphite electrode, which can enhance the reversible capacity of SMG . As a result, UMG delivers the obviously lower discharge capacity than SMG (Figure S11, Supporting Information), which is also probably due to the blocked anion migration path by the substantial direct deposition of electrolyte decomposition products on the surface of graphite electrode.…”
mentioning
confidence: 99%